Frecuencia de prescripción de antibióticos en adultos hospitalizados por SARS-CoV-2 en una institución de alta complejidad en Santiago de Cali, Colombia - Luis Álvaro Melo-Burbano (Asociación Colombiana de Infectología, 2023)
Objective: To determine the frequency of antibiotic use and to know which clinical and socio-demographic variables were related to the probability of suffering infections associated with COVID-19.Methods: Adults hospitalized for COVID-19 who received one or more antibiotics during hospitalization were evaluated. We performed a descriptive analysis of variables in the general population' bivariate analysis in two groups (documented vs. suspected infection) and multivariate logistic regression of factors associated with mortality.Results: It was determined that 60.4% of adults hospitalized for COVID-19 received antibiotics. Coinfection was documented in 6.2% and superinfection in 23.3%. Gram-negative germs were reported in 75.8% of cultures, fungi in 17.8% and gram-positive in 14.2%. Variables such as age, comorbidities, ICU, anemia, steroids, mechanical ventilation, hemofiltration were statistically significantly related to documented infection. High-flow cannula was associated as a protective factor. Overall mortality was 43.9%, 57.8% in the first group and 38.1% in thesecond (p=0.002).Conclusion: There is a considerable frequency of antibiotic use in subjects hospitalized for COVID-19, particularly related to relevant findings of bacterial superin-fection, in those with comorbidities, such as diabetes mellitus, immunosuppression, anemia and fragility, in whom the behavior of the disease is more severe and lethal.